The Effect of Acupressure Point of LI4, PC6, ST25, and ST36 on Increasing the Immunoglobulin and Weight Loss among Toddler - Mery Tresiana Effendi; Diyah Fatmasari; Mateus Sakundarno Adi (Alta Dharma Publisher, 2020)
The eating disorder was a common problem among two-year children. It causes a problem with growth, decreasing immunity, sleep disorder, less aggressiveness, impulsivity, and stunting. The acupressure therapy points of ST36 (Zusanli), CV12 (Zhongwan), SP3 (Taibai), SP6 (San Yinjio), and ST25 (Tianshu) can increase appetite. It was characterized by the rise of immunoglobulin A and weight gain on a toddler. The study aimed to determine the effect of acupressure therapy on Immunoglobulin A(IgA) and weight gain on a toddler. A quasi-experimental, pre-test, and post-test with a non-equivalent control group was applied in this study. A total of 40 samples were recruited using the consecutive sampling, and allocated into the experimental group was 20 samples as well as 20 samples in the control group. Data analyses used were Paired Sample T-Test, Wilcoxon Signed Rank Test, Independent Sample T-Test, and Mann Whitney Test. Acupressure therapy has a significant impact on the toddler's body weight. However, acupressure therapy does not affect immunoglobulin A. Health care institutions can apply acupressure therapy as an alternative treatment to overcome poor nutrition or malnutrition in children under five years old. The community can use acupressure therapy as a solution to handle cases of difficulty increasing weight on toddlers since the method is easy, safe, and economical